Fabrication of bioinspired composite nanofiber membranes with robust superhydrophobicity for direct contact membrane distillation - Fane, Anthony Gordon (2014)
The practical application of membrane distillation (MD) for water purification is hindered by the absence of desirable membranes that can fulfill the special requirements of the MD process. Compared to the membranes fabricated by other methods, nanofiber membranes produced by electrospinning are of great interest due to their high porosity, low tortuosity, large surface pore size, and high surface hydrophobicity. However, the stable performance of the nanofiber membranes in the MD process is still unsatisfactory. Inspired by the unique structure of the lotus leaf, this study aimed to develop a strategy to construct superhydrophobic composite nanofiber membranes with robust superhydrophobicity and high porosity suitable for use in MD. The newly developed membrane consists of a superhydrophobic silica-PVDF composite selective skin formed on a polyvinylidene fluoride (PVDF) porous nanofiber scaffold via electrospinning. This fabrication method could be easily scaled up due to its simple preparation procedures. The effects of silica diameter and concentration on membrane contact angle, sliding angle, and MD performance were investigated thoroughly. For the first time, the direct contact membrane distillation (DCMD) tests demonstrate that the newly developed membranes are able to present stable high performance over 50 h of testing time, and the superhydrophobic selective layer exhibits excellent durability in ultrasonic treatment and a continuous DCMD test. It is believed that this novel design strategy has great potential for MD membrane fabrication.